Which foot first: diversity management and affirmative action in Brazilian business - da Conceição, Eliane; Spink, Peter (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2013)
This paper discusses the relative importance of diversity management programs and government initiatives in reducing job access inequalities. It contrasts the affirmative action-0diversity management process in the USA with that of Brazil, where racial inequality has remained extremely persistent. Using the relational framework (Syed; Özbilgin, 2009) it examines how Brazilian banks are dealing with diversity and affirmative action following initiatives from the Federal Public Prosecutor’s Office for Labor. The results suggest that, individually, neither diversity management nor legal initiatives are sufficient to ensure effective social justice but, in settings of durable inequality, firm legal initiatives are a necessary first step.